SISTEM SAPAAN BAHASA MELAYU DI KECAMATAN TANAH PINOH KABUPATEN MELAWI - Ulya, Cahyati; Sulissusiawan, Ahadi; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The general aim of the research is to describe the Malay language greeting system in Tanah Pinoh District, Melawi Regency. The specific aim is to describe the forms of greetings, various types of greetings, and the use of kinship and non-kinship greetings in Tanah Pinoh District, Melawi Regency. The method used in this research is descriptive method. The form of this research is qualitative. Research data collection was carried out using direct observation techniques, interviews and note-taking. The data sources in this research are native Malay speakers in Melawi Regency, Tanah Pinoh District and the research data are words containing greetings in the Malay community in Batu Begigi Village, Tanah Pinoh District, Melawi Regency. Based on research data, it can be concluded that the form of Malay greetings in Tanah Pinoh District, Melawi Regency is determined based on position, gender, age, family position, speaking situation and birth order. Then, the various Malay greeting words in Melawi Regency, Tanah Pinoh District are determined based on greetings in the family, greetings in society, greetings to people of the same age, greetings to people you don't know, greetings to people who have died, greetings to professions and positions, and greeting in religion. Kinship and nonkinship greetings in Tanah Pinoh District, Melawi Regency are determined based on lineage and marriage line. Then, the output of this research can be a practical guide to make it easier for teachers to teach greetings and build good communication with their students.